Evolução morfoestrutural do Planalto da Ibiapaba (CE/PI) e Noroeste do Ceará, Brasil: interpretações a partir da termocronologia de baixa temperatura - Santos, Francisco Leandro de Almeida (2022)
The Ibiapaba Plateau is a relief compartment, which represents the eastern edge of the Parnaíba Sedimentary Basin in contact with the Borborema Province, presenting glint morphology. Therefore, this research aims to establish interpretations on the morphostructural evolution of the Ibiapaba Plateau and the reliefs of the Northwest of Ceará through thermochronology by traces of fission in apatites. This method allows to build thermal stories that record in geological time the main cooling pulses of the upper crust, allowing to date the events of tectonic reactivation in the upconstruction of escarpments and calculate the rates of denudation of the reliefs. The operational procedures were anchored in field collections, laboratory sample processing, selection of apatite minerals and elaboration of thematic mapping in QGIS 3.18 software. The calculation of ages followed the standards of Soares et al. (2014) by the direct determination of U via LA-ICP-MS. For U determination, natural reference materials were used (MT-7 = 6.9 μg.g–1 U; Dur-2 = 7.5 μg.g–1 U) developed by Soares et al. (2015). The thermal histories of the samples were inferred in the HeFTy 1.8 software proposed by Ketcham (2005), to generate models of hot weather evolution as a function of temperature vs. time. The geomorphological mapping of the area made it possible to identify the relief units, supported by the extraction of ductile and ruptile lineaments and the drainage network for an approach to the genetic, evolutionary and morphostructural conditions. In the results of the analyses, the samples showed ages between Aptian and Albian (Lower Cretaceous), being chrono correlated at the opening of the Atlantic Equatorial Margin. The thermal histories suggest a first cooling event in the samples between the Upper JurassicLower Cretaceous and the Late Cretaceous, generating tectonic reactivation with uplift of the Ibiapaba Plateau and subsequent denudation with rates per sample between 1.00-1.50 km (TFA1), 1.00-1.50 km (TFA4), 1.33-2.00 km (TFA5) and 1.50-2.25 km (TFA6). In the Eocene-Miocene, thermal cooling generated a flexural uplift in the interior of the continent, reestablishing denudation in the Ibiapaba Plateau and in the Peripheral Depression. Denudation achieved rates between 0.83-1.25 km (TFA1), 2.00-3.00 km (TFA4), 1.66-2.50 km (TFA5) and 1.33-2.00 km (TFA6). These data validate the retreat of the glint escarpment and the exhumation of the basement, which by differential erosion, under semi-arid conditions, formed the residual reliefs of the area.